Pharmacoeconomic analysis of using benralizumab for treatment of severe asthma in inpatient and outpatient settings - M. V. Zhuravleva; S. N. Avdeev; Yu. V. Gagarina; T. V. Marin (Фармакоэкономика)
Objective: evaluation of the pharmacoeconomic feasibility of using benralizumab in the form of autoinjector (pen-injector device) in outpatient facilities compared with its use in the form of a syringe in hospital settings for the treatment of severe asthma (SA).Material and methods. The cost minimization and budget impact analysis methods were used. The current practice of treating patients with SA with benralizumab in hospital settings at the expense of compulsory medical insurance funds was compared with the simulated practice. The simulated price was calculated as half patients receiving benralizumab in the hospital transferred to outpatient facilities at the expense of regional funds for 3 years. Direct medical costs included drug cost and outpatient patient monitoring services cost.Results. The direct medical costs associated with benralizumab therapy in outpatient facilities were lower than the costs required for benralizumab therapy in the hospital settings and amounted to 0.99 million rubles versus 1.17 million rubles per one patient per year, respectively. Thus, the use of benralizumab in outpatient facilities leads to savings of 185 thousand rubles (16%). In 2021, 93 patients were prescribed benralizumab in hospital settings. The expansion of the application of benralizumab use in outpatient facilities will lead to a reduction in medical costs in the first year of therapy (when switching 16.7% of patients) by 5.9 million rubles (4,9%). The consistent expansion of the practice of benralizumab use in outpatient facilities over a 3-year horizon (when switching 50% of patients) will lead to a reduction in medical costs by 46.6 million rubles (12.1%).Conclusion. Expansion of benralizumab use in outpatient facilities with a new form of autoinjector (pen-injector device) will lead to savings in medical costs and reduce the burden on the health care system, thus it is economically feasible.